Germinação in vitro de sementes e organogênese indireta do morangueiro - Eidam, Tânia (2012)
Along with blackberry and raspberry, strawberry (Fragaria x ananassa) is part of the group of small red fruits, belonging to the family Rosaceae, the strawberry stands out for the nutritional value and economic importance. Recent years have seen a growth in the Brazilian production of strawberries, however, the participation of Brazil in world production is still low.Aiming to increase production and improve the quality of fruits produced alternatives have been sought, such as better adapted cultivars to the production regions and best seedlings.Considering that the plant tissue culture can be a technique for improvements in this production system, the work was developed aiming to assess the conditions of seed germination of strawberry cv. Camiño Real and to establish protocols for regeneration through organogenesis, to the genetic lineages derived from cultivars Camiño Real and Festival.To assess the conditions of germination, it was used fresh seeds and stored for 2 and 12 months. These were submitted to different treatments of break dormancy and the presence or absence of light during germination. Based on the evaluations of germination rate and fresh weight of the plants obtained, it was concluded that the seed storage significantly reduces the viability thereof, for fresh seeds the treatments of scarification with sandpaper commercial and with sulfuric acid and commercial presented the best results.It was also concluded that the strawberry seeds showed positive photoblastic behavior. For regeneration through organogenesis of genetic lineages obtained from seeds it was used leaf and petiole explants conditioned in culture medium supplemented with different concentrations of growth regulators.The variables evaluated were: percentage of explants with calluses, with buds and shoots, number of buds and shoots per explants, percentage of rooted plants, fresh weight of plants and percentage of plant survival after acclimatization. Through these assessments it was possible to conclude that the leaf explants showed better results for the genotypes tested. The growth regulators recommended are TDZ and AIB, at concentrations of 2,0 mg L-1 and 0,1 mg L-1 respectively, for the lineage obtained from cultivating Camiño Real, and 1,5 mg L-1 and 0,1 mg L-1 respectively, for the lineage derived from the cultivar Festival. The results of seed germination and plant regeneration have shown that it is possible to apply the technique of plant tissue culture for strawberry (FragariaxananassaDuch).